2002
DOI: 10.1111/j.1349-7006.2002.tb01334.x
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of drs mRNA in Colorectal Neoplasms

Abstract: The drs gene was originally isolated as a transformation suppressor gene against the v-src oncogene. Expression of drs mRNA is down-regulated by retroviral oncogenes such as v-src and v-K-ras in the rat cell line F2408. Expression of drs mRNA is also markedly reduced in a variety of human cancer cell lines, including those of carcinomas of the colon, bladder, and ovary, suggesting that down-regulation of drs mRNA is correlated with the development of human cancers. To clarify the correlation between down-regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…This protein has one transmembrane domain, a short intracellular domain in the C-terminus and three consensus repeats (sushi motifs) conserved in the extracellular domain among the selectin family of adhesion molecules and complementbinding proteins (Bevilacqua et al, 1989;Johnston et al, 1989;Reid and Day, 1989;Siegelman et al, 1989;Norman et al, 1991;Lasky, 1992;Kansas, 1996). We also showed that the expression of drs mRNA is markedly downregulated in a variety of human cancer cell lines and malignant tumor tissues, including those of the colon, bladder, ovary, lung, and prostate (Yamashita et al, 1999;Shimakage et al, 2000;Mukaisho et al, 2002;Shimakage et al, 2002;Kim et al, 2003). Introduction of drs cDNA by retrovirus vector into these cancer cell lines suppressed anchorage-independent growth without disturbing cell proliferation.…”
Section: Introductionmentioning
confidence: 91%
“…This protein has one transmembrane domain, a short intracellular domain in the C-terminus and three consensus repeats (sushi motifs) conserved in the extracellular domain among the selectin family of adhesion molecules and complementbinding proteins (Bevilacqua et al, 1989;Johnston et al, 1989;Reid and Day, 1989;Siegelman et al, 1989;Norman et al, 1991;Lasky, 1992;Kansas, 1996). We also showed that the expression of drs mRNA is markedly downregulated in a variety of human cancer cell lines and malignant tumor tissues, including those of the colon, bladder, ovary, lung, and prostate (Yamashita et al, 1999;Shimakage et al, 2000;Mukaisho et al, 2002;Shimakage et al, 2002;Kim et al, 2003). Introduction of drs cDNA by retrovirus vector into these cancer cell lines suppressed anchorage-independent growth without disturbing cell proliferation.…”
Section: Introductionmentioning
confidence: 91%
“…At least three of the chromosome X genes, SLC25A5, SRPX, and RBBP7, which were differentially expressed in any of the EOC cell lines relative to NOSE samples, were also differentially expressed in a comparative HuGeneFL array analysis of low malignant potential ovarian tumors and malignant EOC samples (32). SRPX expression was also downregulated in various cancers including lung (42), colorectal (43), and prostate (44) carcinomas. SRPX was shown to suppress anchorage-independent growth in in vitro assays using a number of human cancer cell lines including an ovarian cell line (45).…”
Section: ------------------------------------------------------------mentioning
confidence: 97%
“…In the present study, downregulation of the expression of SRPX and FLNC was identified, which probably was inhibited by miR-200c-5p or miR-16-5p and miR-205-5p, respectively. SRPX was firstly isolated as a novel transformation suppressor gene, and SRPX expression is downregulated by retroviral oncogenes such as v-src or v-ras (26). Research has demonstrated that SRPX expression is markedly reduced in various human cancer cell lines (26,27).…”
Section: Deg Between Risk Groups ------------------------------------mentioning
confidence: 99%
“…SRPX was firstly isolated as a novel transformation suppressor gene, and SRPX expression is downregulated by retroviral oncogenes such as v-src or v-ras (26). Research has demonstrated that SRPX expression is markedly reduced in various human cancer cell lines (26,27). Tambe et al documented that the C-terminal region and the 3 consensus repeats in the N-terminal region of SRPX are critical in SRPX-induced apoptosis.…”
Section: Deg Between Risk Groups ------------------------------------mentioning
confidence: 99%